[OP.8A.04] DELETION OF THE MAS RECEPTOR AGGRAVATES THE DEVELOPMENT OF ABDOMINAL AORTIC ANEURYSMS BLOOD PRESSURE INDEPENDENTLY IN APOLIPOPROTEIN E-DEFICIENT MICE. (September 2017) - Stegbauer, J.; Yang, G.; Temme, S.; Bruno, S.; Hering, L.; Höges, S.; Rump, L.C.
Abstract : Objective: Hypertension and atherosclerosis are major risk factors for the development of abdominal aortic aneurysms (AAA), a degenerative vascular disease characterized by aortic dilation and rupture leading to sudden death. Currently, the only available treatments are open surgery and endovascular repair, and novel therapeutic targets are needed to prevent AAA. Angiotensin-(1–7) (Ang-(1–7)) has been shown to counteract vascular effects of angiotensin II (Ang II) and improve vascular function via Mas receptor activation. Ang II infusion into apoE-KO mice induces AAA formation. This study investigates the hypothesis that deletion of Mas receptor promotes the development of Ang II-induced AAA. Design and method: ApoE-KO and apoE/Mas-KO mice were infused with Ang II (1000 ng/kg/d) for four weeks. Incidence and extension of AAA were analyzed via ultrasound and magnetic resonance imaging (MRI). Furthermore, aortic injury was assessed by immunhistochemistry, protein- and RNA analysis. Results: Whole-body deficiency of Mas receptor significantly decreased survival proportions. Moreover, Mas receptor deficiency increased AAA incidence and external diameters of suprarenal aortas, from AngII-infused apoE-KO mice. These effects were blood pressure independent as blood pressure measured by radio-telemetry was similar between both groups. Beside an increased intima-media thickness and collagen content, apoE/Mas-KO mice showed increased macrophage infiltration into AAA compared to apoE(KO) mice. MRI studies revealed that AAA and macrophage infiltration begins during the first week of Ang II infusion. To investigate the role of the Mas receptor on macrophages in the development of AAA, we analyzed macrophage function. Here we could show that Mas receptor deficiency accelerated macrophage migration and capacity to polarize pro-inflammatory M1 macrophages in vitro. Furthermore, Mas receptor deficiency was Mas deficiency was associated with pro-inflammatory macrophage cytokine expression, like il-6, inos, ccl2 and il12p40 aortas of apoE-KO mice. Conclusions: In summary, these results demonstrate an important role of the Mas receptor in the development of AAA in apoE-KO mice. Moreover, macrophage function mediated by the Mas receptor seem to regulate the extend of AAA in Ang II infused apoE-KO mice. Thus, activation of the Mas receptor might be a new target in the therapy or prevention of AAA.